Communication of genetic information to at‐risk relatives during the multidisciplinary monitoring of vascular Ehlers–Danlos syndrome in a French referral clinic. Issue 5 (5th January 2020) - Mazzella, Jean‐Michaël; Adham, Salma; Frank, Michael; Legrand, Anne; Lahlou‐Laforêt, Khadija; Jeunemaitre, Xavier
Abstract: Vascular Ehlers–Danlos syndrome (vEDS) is a rare inherited disorder leading to arterial, digestive, and uterine complications due to pathogenic COL3A1 variants. Identification of causal variants allows family screening, provided that relatives have previously been informed, according to a 2013 French Decree. The aims of our study were to assess the communication of genetic information to at‐risk relatives, the impact of diagnosis disclosure and to highlight a possible link between the experience of vEDS patients and ability to communicate about genetic information. A total of n = 51 vEDS adult probands answered a questionnaire during a clinical visit. Communication to relatives was considered effective if the proband gave information to some or all first‐degree relatives and considered easily achieved if it was disclosed to all relatives less than a month after the diagnosis and without difficulty. Personal and family vEDS experiences of probands were also assessed. Effective communication of information to relatives was remarkably high (98%). Siblings were the most frequently informed relatives (82%). Women informed their at‐risk relatives of genetic family screening faster ( p = .006) and easier ( p = .004) than men. There was no difference in the disclosure of information to relatives before and after 2013 in our multidisciplinary clinic. Regarding the lived experience of vEDS patients, they felt anxious (78%) at diagnosis disclosure but also considered this diagnosis as an opportunity to start a medical follow‐up (82%) putting an end to diagnosis delay. Our findings highlight for the first time that the ability to easily inform at‐risk first‐degree relatives is related to the relief felt during vEDS‐positive diagnosis disclosure ( p = .04). In order to improve the communication of genetic information to relatives, we believe that psychological support should systematically be part of the multidisciplinary monitoring, just as medical follow‐up and genetic counseling.